2001
DOI: 10.1021/jo010944m
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Structures and Stabilities of the Dimer of Ethyl Cation, (C2H5+)2 and Related C4H102+ Isomers1

Abstract: Ab initio calculations at the MP4(SDTQ)/6-311G//MP2/6-31G level were performed to study the structures and stabilities of the dimer of ethyl cation, (C(2)H(+)(5))(2), and related C(4)H(10)(2+) isomers. Two doubly hydrogen bridged diborane type trans 1 and cis 2 isomers were located as minima. The trans isomer was found to be more favorable than cis isomer by only 0.6 kcal/mol. Several other minima for C(4)H(10)(2+) were also located. However, the global energy minimum corresponds to C-H (C(4) position) protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Structures and stabilities of the ethyl cation dimer have been studied at high levels of electron correlation (MP4(SDTQ)) by Olah and co-workers. 33 They found two minima, 43a and 43b, roughly equal in energy. Both structures lie over 130 kJ mol Ϫ1 higher in energy than the C 4 H 10 2ϩ global minimum, protonated 2-butyl cation 44.…”
Section: Structures and Stabilitiesmentioning
confidence: 98%
“…Structures and stabilities of the ethyl cation dimer have been studied at high levels of electron correlation (MP4(SDTQ)) by Olah and co-workers. 33 They found two minima, 43a and 43b, roughly equal in energy. Both structures lie over 130 kJ mol Ϫ1 higher in energy than the C 4 H 10 2ϩ global minimum, protonated 2-butyl cation 44.…”
Section: Structures and Stabilitiesmentioning
confidence: 98%
“…ethyl cation be well-known [38,39]. Interestingly, a large number of theoretical studies of the ethyl cation and its hyperconjugation effect have been reported, including the classic work done by Pople [40][41][42] and others [43][44][45]. However, Zuilhof et al [46] and Carneiro et al [47] analyzed the molecular geometry of ethyl cation using the MP2(FULL)/6-31G(d,p) and B3LYP/6-311G(d,p) calculations.…”
Section: Optimized Geometrymentioning
confidence: 99%
“…8 The related dimer of the ethyl cation (C 4 H 10 2+ dication) was recently investigated by Olah, Prakash, and Rasul at the ab initio MP2/6-31G** level. 9 Several doubly hydrogen bridged structures including the dimethyl analogue of C 2 H 6 2+ (D 2d symmetric structure, Chart 3) were found to be minima. Previously, we were able to show by hydrogen/deuterium exchange experiments and by theoretical calculations that long-lived stable tert-butyl 10 as well as isopropyl 11 cations undergo C-H protonation in superacids to form highly electron deficient protio-tert-butyl (C 4 H 10 2+ ) and protioisopropyl (C 3 H 8 2+ ) dications, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The related dimer of the ethyl cation (C 4 H 10 2+ dication) was recently investigated by Olah, Prakash, and Rasul at the ab initio MP2/6-31G** level . Several doubly hydrogen bridged structures including the dimethyl analogue of C 2 H 6 2+ ( D 2 d symmetric structure, Chart ) were found to be minima.…”
Section: Introductionmentioning
confidence: 99%